A pilot study of calling patterns and vocal turn-taking in wild bonobos Pan paniscus. Issue 3 (4th May 2022) - Cornec, Clément; Ngofuna, Muzungu; Lemasson, Alban; Monghiemo, Claude; Narat, Victor; Levréro, Florence
Highlights: This pilot study shows that wild bonobos display the fundamental temporal rules of vocal turn-taking Occurrences of calling patterns are in line with the unique observation collected from a captive group Calling patterns do not differ significantly with age and sex Calling patterns appear context-dependent In several species of non-human primates, non-agonistic vocal exchanges can be seen as a primitive form of conversation, as they respect basic temporal rules (i.e. turn-taking, overlap avoidance), the same as those that guide human conversations. Conversational rules have recently been suggested in captive great ape species, yet the only study investigating vocal turn-taking in wild great apes did not find any evidence of such vocal roles. Whether the environmental conditions (captivity versus free ranging) or the social organisation of a given species shape temporally ruled vocal exchanges remain open questions. Here, we investigated general calling patterns of peaceful vocal exchanges in a wild bonobo community. This pilot study revealed that wild bonobos respect the fundamental temporal rules of vocal turn-taking, namely the avoidance of overlapping and the presence of short call-intervals between interlocutors on the order of 2 sec, corroborating findings from captive bonobos. Despite the limited sample size, our finding suggests that vocal exchanges appear context-dependent but neither age nor sex seem to influence their occurrence. While further studies are needed to confirm these observations, this study helps to fill a major gap in research on the vocal communication of wild great apes, paving the way for more extensive comparative studies, representing a further step towards a better understanding of how vocal turn-taking arose in humans.